Indonesia’s Humanitarian Diplomacy in Jordan: The Role of the Indonesian Embassy in Amman in Facilitating Aid for Palestinian Refugees - Daepulloh; Alfy Isya Muharam; Ali Maksum (Department of Political Science - Universitas Sains Al-Qur’an, 2026)
This study examines the role of the Embassy of the Republic of Indonesia in Amman, Jordan, as an implementing actor of Indonesia's humanitarian diplomacy following the escalation of the Gaza conflict in October 2023. Employing a qualitative approach with a case study design, this research analyzes how the Indonesian Embassy in Amman transformed from a bureaucratic facilitator into a humanitarian broker within a multinational aid ecosystem. Utilizing the framework of Constructivism by Alexander Wendt, this study argues that the successful distribution of 32 container trucks of aid, achieved through the coordination among the Nusantara Palestina Center, BAZNAS, the National Agency for Disaster Countermeasure, and the Jordan Hashemite Charity Organization, is a concrete implementation of the national identity and normative solidarity that constructs Indonesia's foreign policy interests and behavior. Distinct from the Realist approach, which assumes states act purely out of material calculations, this study finds that national identity directly dictates the operational decisions of diplomats on the ground. The post-October 7 conditions fundamentally altered the operational architecture of humanitarian aid, and the Embassy adapted through the physical presence of its Political Attaché as a field monitor at critical border crossing points to fulfill this state identity mandate amidst high risks.